Photodegradation of Crystal Violet Dyes Using Fe2O3/CuO with the Addition of MEA Additive - Alya Ramadhani; Hary Sanjaya; Edi Nasra; Fitri Amelia (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2026)
Synthetic dyes, including Crystal Violet (CV), are widely used in the textile and chemical industries and are increasingly released into the environment due to their toxic, mutagenic, and non-biodegradable nature. The purpose of this work is to examine the photocatalytic degradation of CV utilising Fe2O3/CuO heterojunction with monoethanolamine (MEA) as an additive. To maximise its optical and catalytic capabilities, the Fe2O3/CuO photocatalyst was synthesised using different CuO compositions and MEA volumes. Using UV-Visible Diffuse Reflectance Spectroscopy (UV-DRS) and the Kubelka-Munk technique, the band gap energy was determined. According to the findings, the incorporation of CuO did not show a pronounced effect, but it may contribute to the photocatalytic system through interfacial interactions and improved charge transfer within the Fe2O3/CuO structure. The lowest band gap value and optimal composition were found at 20% CuO, which was further reduced by adding 2 mL MEA. Tests of photocatalytic activity were conducted for 120 minutes when exposed to UV and sunshine. The results showed that CV had a high deterioration efficiency, reaching about 53.87% when exposed to sunshine. The creation of a Fe2O3/CuO heterojunction, which enhances charge separation and decreases electron-hole recombination, is responsible for the improved performance, whereas MEA enhances particle distribution and increases surface area. These results suggest that Fe2O3/CuO with MEA is a promising, economical, and eco-friendly photocatalyst for the treatment of wastewater contaminated with dyes.